Tuning the electronic and optical properties of graphane/silicane and fhBN/silicane nanosheets via interfacial dihydrogen bonding and electrical field control. Issue 38 (12th September 2016) - Jiang, Junke; Liang, Qiuhua; Zhang, Shengli; Meng, Ruishen; Tan, Chunjian; Yang, Qun; Sun, Xiang; Ye, Huaiyu; Chen, Xianping
Abstract : The electronic and optical properties of graphane/silicane and fhBN/silicane nanosheets were systematically investigated using density functional theory calculations. Abstract : In this work, using density functional theory (DFT) with van der Waals (vdW) corrections, the effects of dihydrogen bonding on the stability, electronic and optical properties of a graphane/silicane heterobilayer and a fully hydrogenated hexagonal boron nitride (fhBN)/silicane heterobilayer were investigated. Our results reveal that dihydrogen bonding at the interface (C–H⋯H–Si, N–H⋯H–Si or B–H⋯H–Si) would induce interface polarizations, which greatly modulate the electronic and optical properties of the heterobilayers. Moreover, the stability and electronic properties of the graphane/silicane heterobilayer and the fhBN/silicane heterobilayer can be tuned with electric fields (E-fields), yielding not only the band gap of the heterobilayers in a semiconductor–metal transition but also widely tunable binding strengths. More importantly, the mobilities of the graphane/silicane heterobilayer and the fhBN/silicane heterobilayer we predicted are electron-dominated, reasonably high (improvable up to 170 cm 2 V −1 s −1 for the graphane/silicane heterobilayer and ∼550 cm 2 V −1 s −1 for the fhBN/silicane heterobilayer along the Γ – M direction) and extremely anisotropic. Furthermore, we analysed the dielectric function and the absorption coefficient, and it is evident that the optical properties of the heterobilayers show a much larger spectral range compared with the isolated graphane, fhBN and silicane, especially the fhBN/silicane heterobilayer showing enhanced visible light absorption. These results offer new opportunities for developing electronic and opto-electronic devices based on the graphane/silicane heterobilayer and the fhBN/silicane heterobilayer. More importantly, our findings pave the way for investigating the effect of dihydrogen bondings not only on the electronic properties but also on the opto-electronic properties of the composite hydrogenated materials.